2015
DOI: 10.2514/1.g000634
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Autonomous Visual Vertical Control of a Quadrotor Unmanned Aerial Vehicle

Abstract: Near ground maneuvers, such as hover, approach and landing, are key elements of autonomy in unmanned aerial vehicles. Such maneuvers have been tackled conventionally by measuring or estimating the velocity and the height above the ground often using ultrasonic or laser range finders. Near ground maneuvers are naturally mastered by flying birds and insects as objects below may be of interest for food or shelter. These animals perform such maneuvers efficiently using only the available vision and vestibular sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…This is indicated for the (approximations to) the values of K z at which the system becomes unstable (w 1 = -). 1 The constancy of this relation depends on the constancy of the robot's mass, which applies for landing quad rotors but not for spacecraft. A spacecraft will loose more and more mass when landing, hence aggravating the effect in equation (13).…”
Section: Fundamental Reason For Gain Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is indicated for the (approximations to) the values of K z at which the system becomes unstable (w 1 = -). 1 The constancy of this relation depends on the constancy of the robot's mass, which applies for landing quad rotors but not for spacecraft. A spacecraft will loose more and more mass when landing, hence aggravating the effect in equation (13).…”
Section: Fundamental Reason For Gain Tuningmentioning
confidence: 99%
“…The key to this success is that flying insects follow straightforward strategies based on optical flow observables. First, it was found that honeybees keep ventral flow (defined as x [1,24,26,28]. These strategies either enforce a decreasing time-to-contact (as humans do for car braking [30]) or keep the divergence constant (as honeybees do for straight landings [3]).…”
Section: Introductionmentioning
confidence: 99%
“…On-board the UAV were also mounted a sonar and an optic flow sensor for altitude, position and velocity control. In [44] a novel strategy for close distance to the ground VTOL-UAV manoeuvring like hovering around, landing and approaching a target has been described. The framework of the time-to-contact (tau) theory has been implemented for autonomous navigation.…”
Section: Vision Based Controlmentioning
confidence: 99%
“…Ventral flows may also be used for hover stabilization to augment visual vertical control. 29 In recent aerial robotic applications, mainly visual observables based on vertical motion were applied, allowing control of vertical dynamics independent of horizontal motion. One of these observables is flow-field divergence D, i.e., the ratio of vertical velocity to height.…”
Section: Landing Using Optical Flowmentioning
confidence: 99%